(untitled) (Journal of the Bangladesh Agricultural University, 2014)
This paper is an endeavor to depict the reasons for migration and involving with garments industry, adequacy, sources and utilization of credit, and empowerment of the female garments workers in a selected area of Dhaka City. Primary data were collected from 60 respondents in two categories such as: 30 helpers and 30 operators, randomly. Descriptive statistics such as percentage and arithmetic mean were applied to analyze the data and to describe socioeconomic characteristics of the respondents. Poverty, search for job and husbands work in Dhaka, financial help to family, secure more income and assure basic needs were the main reasons for involving with garments industry. Average amount applied for loan was Tk. 5650.00 and average amount of loan received was Tk. 4450.00 which was 78.23% of total applied amount in the category of Helper. On the other hand, average amount applied for loan was Tk. 10540.00 and average amount of loan received was Tk. 7670.00 which was 72.77% of total applied amount in the category of Operator. About 94% respondents (Helper) keep their earnings and spend independently; this figure was about 97% for operator. Level of income, human and social capital improved in both helper and operator categories but savings decreased 66.67% and 40% respectively. In the areas of decision making like food selection, treatment, visit to relatives, family planning all the cases vastly improved. This study recommended measures for improving the prevailing microfinance facilities, to a great extent, to achieve female workers empowerment and satisfaction at the maximum level. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18223 J. Bangladesh Agril. Univ. 11(1): 125-132, 2013